The Mediating Role of Risk Perception in the Relationship between Risk Propensity and Investment Decisions among Millennials in Indonesia - Asri Solihat; Nugraha Nugraha; Disman Disman; Ikaputera Waspada (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This study aims to explore the relationship between risk propensity, risk perception, and investment decisions among millennials in West Java, Indonesia. The study particularly examines how risk perception mediates the relationship between risk propensity and investment choices.Methodology: A purposive sampling method was used, with 500 respondents from the millennial generation, aged 24-39 years, who have at least one year of experience in investments. The data was collected via online surveys and analyzed using correlation and mediation analysis with Process v.34 by Andrew F. Hayes.Findings: The results demonstrate that risk propensity has a direct positive effect on investment decisions. Additionally, risk perception significantly mediates the relationship between risk propensity and investment decisions. Millennials with higher risk propensity tend to make more risk-taking investment decisions, but the level of their risk perception influences the final decision-making process.Conclusion: This research contributes to a deeper understanding of how risk behaviors, particularly risk propensity and perception, shape investment decisions among millennials. It provides valuable insights for investors and practitioners in the field of digital investment, suggesting that fostering better risk perception could lead to more informed investment decisions.